Implication of MATE2, OCT2 and ATM genes polymorphism and their association with metformin efficacy and glycemic control in type 2 diabetes mellitus patients - Raza, Muhammad Kashif; Aamir, Aziz-Ul-Hasan; Shahwar, Durr-E; Usama,; Mansour, Lamjed; Khan, Zahid; Ali, Aktar; Imran, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2025)
In type 2 diabetes mellitus (T2DM) patients, metformin, the drug of choice, exhibits variable therapeutic response attributed to gene polymorphism. The current study aimed to investigate the association of MATE2 rs12943590, OCT2 rs7757336, and ATM rs11212617, which are hotspot single-nucleotide polymorphisms (SNPs), with metformin efficacy and glycemic control in T2DM patients. A total of 417 study subjects were enrolled, consisting of 217 newly diagnosed and drug-naive T2DM patients, while 200 individuals were healthy controls. Patients were further divided into two subgroups: metformin responsive and metformin-non-responsive individuals. Study patients were kept on exclusive metformin monotherapy for three successive months. Patients’ basic parameters like age, fasting glucose, HbA1c, LDL, HDL, Cholesterol, and BMI were recorded. Real-time PCR involving melt curve analysis and subsequent agarose gel electrophoresis with Sanger sequencing was employed for genotype analysis. MATE2 (SLC47A2) rs12943590 GA genotype (OR 0.44, CI 95% 0.23-0.86, p = 0.01), OCT2 (SLC22A2) rs7757336 GG genotype (OR 5.82, 95% CI 1.40-24.24, p = 0.01), and G allele (OR 2.21, CI 95% 1.18-4.14, p = 0.01) were significantly associated with metformin response and glucose-lowering effect. No significant association (p > 0.05) was observed for ATM rs11212617.